A 5-dimensional Tonnetz for nearly symmetric hexachords. Issue 1 (2nd January 2022) - Mohanty, Vaibhav
Abstract : The standard 2-dimensional Tonnetz describes parsimonious voice leading connections between major and minor triads as the 3-dimensional Tonnetz does for dominant seventh and half-diminished seventh chords. In this paper, a 5-dimensional Tonnetz is introduced, providing a geometric framework for parsimonious voice leading among nearly symmetric hexachords of the mystic-Wozzeck genus. Cartesian coordinates for points on this discretized grid, generalized coordinate collections for the vertices of the 5-simplices corresponding to mystic and Wozzeck chords, and the geometric nearest-neighbours of a selected chord are derived.